X-ray spectroscopic study of the electronic structure of CuCrO2 - Arnold, T; Payne, D; Bourlange, A; Hu, J; Egdell, R; Piper, L; Colakerol, L; De Masi, A; Glans, P; Learmonth, T; Smith, K; Guo, J; et al. (2009)
The electronic structure of the p -type transparent conducting oxide CuCrO2 has been studied by x-ray photoemission, x-ray absorption, and x-ray emission spectroscopies. The upper part of the valence band derives mainly from Cu3d and Cr3d states while the lower valence-band states are of dominant O2p atomic character, but with pronounced mutual hybridization among Cu3d, Cr3d, and O2p states. Site specific electronic excitations have been studied by resonant inelastic x-ray scattering at the CuL and CrL edges. Inelastic loss at the CuL edge is dominated by on-site interband excitations similar to those found in Cu2 O, while at the CrL edge localized excitations arising from ligand field splitting of the Cr3d levels are observed. Mg doping on the Cr sites in CuCrO2 is shown to lead to a pronounced shift in the Fermi level toward the edge of the valence band. The experimental data are compared to electronic structure calculations on CuCrO2 carried out using density-functional methods corrected for onsite Coulomb repulsion. © 2009 The American Physical Society.